(untitled) (Palíndromo, 2025)
In this text, we intend to reflect on the term “listening” in the field of art, bringing together and putting into dialogue four distinct, non-exclusive perspectives. The first addresses the limits between the arts, highlighting their mobility, according to Pareyson and authors linked to comparative aesthetics (Souriau, Bosseur, Dénizeau, Freitas). The second brings the notion of “synesthesia”, from the perspective of science (Bergantini, Sacks) and phenomenology (Merleau-Ponty, Caznok) and how it can apply to the artistic context, especially in the relationships between hearing and vision. Next, we focus on the meaning of “image”, as a common denominator of varied sensory experiences, based mainly on Iazzetta. Finally, the particularities in Szendy’s understanding of listening, such as “writing” and “arrangement”, are exposed. These perspectives – which call upon different concepts and meanings – complement each other in the hope of reinforcing a broader understanding of listening and, who knows, fostering new research and artistic creations.